Second order slip micropolar MHD hybrid nanofluid flow over a stretching surface with uniform heat source and activation energy: Numerical computational approach - Syed Arshad Abas; Hakeem Ullah; Mehreen Fiza; Ali Akgul; Aasim Ullah Jan; Magda Abd El-Rahman; Seham M. Al-Mekhlafi (Results in Engineering)
Applications: Micropolar fluids are extensively used in lubrication, polymer processing, and heat transfer applications to enhance performance in systems with suspended microstructures. These fluids find applications in industries such as medical, chemical, and microfluidics. Recent advancements have highlighted the potential of hybrid nanofluids in further improving thermal and flow characteristics. Novelty: Motivated by these developments, this study investigates the heat and mass transfer characteristics of a micropolar hybrid nanofluid comprising titanium dioxide (TiO2) and silver (Ag) nanoparticles suspended in water. The analysis focuses on the effects of slip boundary conditions, Joule heating, thermal radiation, heat sources, magnetohydrodynamic (MHD) effects, activation energy, and binary chemical reactions. Methodology: A mathematical model is formulated based on boundary-layer approximations, leading to a system of partial differential equations (PDEs) that describe the flow, thermal, and concentration fields. These PDEs are subsequently transformed into a set of ordinary differential equations (ODEs) using similarity transformations. The resulting higher-order nonlinear ODEs are solved numerically using the bvp4c technique in MATLAB. Findings: The results reveal that the inclusion of slip boundary conditions significantly influences the flow dynamics, reducing skin friction by 4.9 % and 10.4 % with increasing magnetic and material parameters, respectively, but enhancing it with a higher slip factor by 18.88 %. Additionally, an increased volume fraction of nanoparticles elevates the heat transfer rate by 6.3 % while diminishing the Sherwood number by 2.6 %, showcasing the thermal enhancement capabilities of the hybrid nanofluid. This study contributes to the field by providing new insights into the combined effects of Joule heating, activation energy, and chemical reactions on micropolar hybrid nanofluid flow. The result of bvp4c compared with previous literature and found to be closely aligned with published work. The findings have implications for the optimization of thermal management systems and processes in advanced engineering and industrial applications.